High‐Efficiency Air‐Processed Si‐Based Perovskite Light‐Emitting Devices via PMMA‐TBAPF6 Co‐Doping. Issue 11 (24th March 2022) - Xu, Xiaoxiao; Zhu, Ting; Xiao, Ke; Zhu, Yu; Chen, Jiaming; Li, Dongke; Xu, Ling; Xu, Jun; Chen, Kunji
Abstract: The preparation of high‐efficiency perovskite light‐emitting devices (PeLEDs) in the air‐ambient has always been a challenge. Herein, the authors propose a Si‐based near‐infrared air‐processed PeLED through the anti‐solvent engineering. Two materials, poly(methyl methacrylate) (PMMA) and tetrabutylammonium hexafluorophosphate (TBAPF6 ) are co‐doped into the anti‐solvent, the former protects the perovskite from degradation in a high‐humidity atmosphere, and the latter passivates the defects on perovskite surface and increases the conductivity. Through the anti‐solvent engineering, the efficiency of PeLEDs has been significantly enhanced and obtains a maximum external quantum efficiency (EQE) of 10.4%, which is the highest among similar devices. This work shows that it is possible to prepare high‐efficiency near‐infrared PeLEDs in air‐ambient through a simple method. Abstract : Efficiency and stability of the air‐processed Si‐based near‐infrared perovskite light‐emitting devices have been enhanced by anti‐solvent engineering. PMMA and TBAPF6 are co‐doped in anti‐solvent to passivate defects and protect perovskite in air‐ambient. With the co‐doped perovskite, the efficiency of the device increases to 10.4% with a half‐life of over 50 min.